2018
DOI: 10.1007/s40430-018-1144-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of relation between the 3D printer laser beam power and the surface morphology properties in Ti-6Al-4V titanium alloy parts

Abstract: Additive technologies are increasingly widespread in the aviation industry, medicine and implantology. It is essential that the parts manufactured for these applications meet the highest requirements not only as far as their strength, but also surface quality. Thus, high importance should be attached to performing analysis of the manufactured part's surface morphology to ensure optimised functionality, and to selecting appropriate post-processes so as to arrive at the required external surface structure. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 40 publications
(38 reference statements)
0
27
0
Order By: Relevance
“…The analysis of the impact of technological parameters of SLM laser additive technology on the quality of the geometric structure of the surface is described in [15]. The authors, using the InfiniteFocus optical microscope, tested the surfaces without frontal and lateral specimens made of Ti-6Al-4V material.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the impact of technological parameters of SLM laser additive technology on the quality of the geometric structure of the surface is described in [15]. The authors, using the InfiniteFocus optical microscope, tested the surfaces without frontal and lateral specimens made of Ti-6Al-4V material.…”
Section: Introductionmentioning
confidence: 99%
“…References [ 28 , 29 , 30 ] present the problem of cleaning machine parts and methods of their protection. At last, the sources of corrosion processes and corrosion prevention methods were evaluated in References [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that interconnectivity and porosity are essential to promote cell culture, tissue growth, loading and migration of cells, tissue growth, and flow of body fluid [10][11][12][13]. At present, a number of researchers [5,6,[14][15][16][17][18][19][20][21] are working with non-conventional techniques and state-of-the-art fused deposition modeling (FDM) is one of them. This technique has been becoming most popular in biomedical field owing to its high flexibility of producing different shaped implants, 3D faxing, and green manufacturing nature.…”
Section: Introductionmentioning
confidence: 99%